Prospective Evaluation of the Association Between Arthritis and Cognitive Functions in Middle-Aged and Elderly Chinese - Liu, Wenyu; Yang, Xue; Jin, Xingzhong; Xiu, Peng; Wen, Ying; Wu, Nianwei; Zhao, Jian; Zhou, Dong; Pan, Xiong-Fei (Frontiers in Aging Neuroscience, 2021)
Background: Assessing the relation between arthritis and cognitive impairment could expand the understanding of health consequences of arthritis. The aim was to prospectively examine the association between arthritis and cognitive functions among middle-aged and elderly Chinese. Methods: Our analyses were based on data from the nationwide China Health and Retirement Longitudinal Study (2011-2016). Arthritis was ascertained by self-reported doctor diagnosis during the baseline survey. Cognitive functions were evaluated in three domains including episodic memory, mental status, and global cognition. Linear mixed models were employed to assess the association between baseline arthritis and cognition functions. Results: Of 7,529 Chinese adults, 49.79% were men, and mean age was 57.53 years. During a follow-up of 4 years, participants with baseline arthritis showed lower scores of episodic memory [β= -0.08; 95% confidence interval (CI): -0.14, -0.03], mental status (β=-0.14; 95% CI: -0.22, -0.05), and global cognition (β=-0.22; 95% CI: -0.34, -0.11), compared to those without arthritis. In addition, participants with arthritis showed increased rates of decline in mental status and global cognition by 0.04 (95% CI: 0.01, 0.08) and 0.05 (95% CI: 0.01, 0.09) units per year, respectively. Conclusion: Arthritis was associated with subsequent risk of poorer cognitive functions and slightly faster declines in cognitive functions among Chinese middle-aged and elderly adults. Our findings should be confirmed in future large prospective studies in Chinese and other populations.